Oral health literacy improvement among adolescents and toddlers and early detection of toddler oral health as baseline data for empowerment: Study cross-sectional - Suwargiani, Anne Agustina; Putri, Fidya Meditia; Hamdani, Ardena Maulidia; Yubiliana, Gilang; Setiawan, Asty Samiaty; Susilawati, Sri; Zubaedah, Cucu; Suryanti, Netty (Fakultas Kedokteran Gigi Universitas Padjadjaran, 2026)
ABSTRACTIntroduction: Community empowerment is essential in Indonesia due to the limited number of health professionals, their uneven distribution, and the low level of oral health literacy in the population. Empowerment efforts should reach all population groups and align with the Healthy Indonesia 2030 agenda, which emphasizes preventive and promotive services within a continuum of care framework. The aim of this study is to evaluate the improvement of oral health literacy through various empowerment strategies among adolescents, and to conduct early detection of oral health conditions in toddlers as baseline data for empowerment initiatives. Methods: This study used an experimental pretest and posttest design with four community empowerment approaches, including oral health literacy improvement through crossword puzzles and HELD-14 based playing cards, education on cariogenic foods for adolescents and toddlers, early detection of oral health conditions in toddlers, and a 21 day good oral health habit counseling program combined with dental screening for toddlers. Participants were selected using purposive sampling. Inclusion criteria were willingness to participate, ability to read and write, and absence of hearing or speech impairments. Exclusion criteria included absence during the intervention activities and incomplete questionnaire responses or dental examinations. Data were analyzed using the Shapiro Wilk and Kolmogorov Smirnov tests for normality, followed by independent t tests and Mann Whitney tests. Results: Empowerment interventions among adolescent communities using crossword puzzles, HELD-14 based playing cards, education on cariogenic foods, and the 21 day good habit counseling program demonstrated a significant improvement in oral health literacy. Early detection results showed a significant difference in oral health status among toddlers between males and females. Conclusion: Significant differences were observed between pretest and posttest results across the four community empowerment approaches.KEY WORDS: empowerment, literacy, education, oral health status, continuum of carePeningkatan literasi kesehatan gigi melalui berbagai metode pemberdayaan pada komunitas remaja, balita dan deteksi dini kesehatan gigi anak balita sebagai data dasar pemberdayaan: Studi cross-sectionalABSTRAKPendahuluan: Upaya pemberdayaan masyarakat sangat perlu dilakukan, karena masih terbatasnya tenaga kesehatan di Indonesia dan persebarannya tidak merata serta literasi kesehatan gigi dan mulut di masyarakat masih kurang. Upaya pemberdayaan harus menjangkau segala lapisan masyarakat dan bergerak ke arah Indonesia sehat tahun 2030 yang lebih mengupayakan preventif promotif dalam melakukan pelayanan berbasis continuum of care. Tujuan penelitian menganalisis peningkatan literasi kesehatan gigi melalui berbagai metode pemberdayaan pada komunitas remaja, balita dan deteksi dini kesehatan gigi anak balita sebagai data dasar pemberdayaan. Metode: Pendekatan eksperimen jenis pretest posttest design dengan 4 metode pemberdayaan peningkatan literasi teka-teki silang dan kartu bermain berbasis held 14 dan peningkatan literasi mengenai makanan kariogenik pada remaja dan anak balita dan dan deteksi dini kesehatan gigi pada anak balita, penyuluhan kebiasaan baik 21 hari dan deteksi dini kesehatan gigi anak balita. Jumlah sasaran diperoleh melalui purposive sampling dengan penentuan kriteria inklusi yaitu responden yang mengikuti pemberdayaan, dapat membaca dan menulis serta tidak ada gangguan pendengaran atau bicara. Kriteria ekslusi adalah responden yang tidak hadir pada saat kegiatan, tidak melakukan pengisian kuisioner/pemeriksaan dengan lengkap. Analisis data dilakukan dengan uji normalitas shapiro Wilk dan Kolmogorov Smirnov serta uji beda t-test dan Mann-Whitney. Hasil: Pemberdayaan pada komunitas remaja dengan literasi teka-teki silang dan kartu bermain berbasis held 14, peningkatan literasi mengenai makanan kariogenik dan penyuluhan kebiasaan baik 21 hari menunjukkan peningkatan literasi yang signifikan. Hasil deteksi dini menunjukkan terdapat perbedaan signifikan kesehatan gigi anak balita antara laki laki dan perempuan. Simpulan: Terdapat perbedaan antara hasil pretest dan postest pada ketiga metode pemberdayaan yaitu literasi remaja dan anak balita dan terdapat perbedaan status kesehatan gigi antara laki-laki dan perempuan.KATA KUNCI: pemberdayaan, literasi, edukasi, status Kesehatan gigi, continuum of care